Psoas compartment and sacral plexus block via electrostimulation for pelvic limb amputation in dogs. (July 2017) - Congdon, Jonathon M.; Boscan, Pedro; Goh, Clara S.S.; Rezende, Marlis
Abstract: Objective: To assess the efficacy of psoas compartment and sacral plexus block for pelvic limb amputation in dogs. Study design: Prospective clinical study. Animals: A total of 16 dogs aged 8 ± 3 years and weighing 35 ± 14 kg (mean ± standard deviation). Methods: Dogs were administered morphine (0.5 mg kg −1 ) and atropine (0.02 mg kg −1 ); anesthesia was induced with propofol and maintained with isoflurane. Regional blocks were performed before surgery in eight dogs with bupivacaine (2.2 mg kg −1 ) and eight dogs were administered an equivalent volume of saline. The lumbar plexus within the psoas compartment was identified using electrolocation lateral to the lumbar vertebrae at the fourth–fifth, fifth–sixth and sixth–seventh vertebral interspaces. The sacral plexus, ventrolateral to the sacrum, was identified using electrolocation. Anesthesia was monitored using heart rate (HR), invasive blood pressure, electrocardiography, expired gases, respiratory frequency and esophageal temperature by an investigator unaware of the group allocation. Pelvic limb amputation by coxofemoral disarticulation was performed. Dogs that responded to surgical stimulation (>10% increase in HR or arterial pressure) were administered fentanyl (2 μg kg −1 ) intravenously for rescue analgesia. Postoperative pain was assessed at extubation; 30, 60 and 120 minutes; and the morning after surgery using a visual analog scale (VAS). Results: The number of intraoperative fentanyl doses was fewer in the bupivacaine group (2.7 ± 1.1 versus 6.0 ± 2.2; p  < 0.01). Differences in physiologic variables were not clinically significant. VAS scores were lower in bupivacaine dogs at extubation (0.8 ± 1.9 versus 3.8 ± 2.5) and at 30 minutes (1.0 ± 1.4 versus 4.3 ± 2.1; p  < 0.05). Conclusions and clinical relevance: Psoas compartment (lumbar plexus) and sacral plexus block provided analgesia during pelvic limb amputation in dogs.